1999
DOI: 10.1172/jci3620
|View full text |Cite
|
Sign up to set email alerts
|

Maleic acid and succinic acid in fermented alcoholic beverages are the stimulants of gastric acid secretion

Abstract: Only during the last 15 years have systematic and controlled studies on the action of pure ethanol and some commonly ingested alcoholic beverages on gastric acid secretion and release of gastrin in humans been published (1)(2)(3)(4)(5)(6)(7)(8). Pure ethanol in low concentrations (≤4% vol/vol) is a mild stimulant of gastric acid output, whereas at higher concentrations, it has either no effect or a mildly inhibitory one (5). Alcoholic beverages with low ethanol content (beer and wine) are powerful stimulants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 14 publications
1
42
0
4
Order By: Relevance
“…Oczywistą implikacją tej obserwacji jest dąże-nie do zidentyfikowania w napojach alkoholowych związków chemicznych odpowiedzialnych za działanie stymulujące sekrecję w żołądku. Według badaczy niemieckich są to powstające w procesie fermentacji z udziałem drożdży kwasy maleinowy i bursztynowy [60], natomiast badacze japońscy wyodrębnili z piwa N-metylotyraminę, odpowiedzialną za stymulację sekrecji i uwalnianie gastryny [61].…”
Section: Wpływ Napojów Alkoholowych Na żOłądekunclassified
“…Oczywistą implikacją tej obserwacji jest dąże-nie do zidentyfikowania w napojach alkoholowych związków chemicznych odpowiedzialnych za działanie stymulujące sekrecję w żołądku. Według badaczy niemieckich są to powstające w procesie fermentacji z udziałem drożdży kwasy maleinowy i bursztynowy [60], natomiast badacze japońscy wyodrębnili z piwa N-metylotyraminę, odpowiedzialną za stymulację sekrecji i uwalnianie gastryny [61].…”
Section: Wpływ Napojów Alkoholowych Na żOłądekunclassified
“…Beginning in the early 1980s and using systematic and controlled examinations on the effect of pure ethanol and commonly ingested alcoholic beverages on gastric acid secretion, Singer and co-workers as well as others [38,39,40,41,42,43,44,45,46] found that the effect of ethanol and alcoholic beverages on gastric acid secretion in healthy humans is differentiated after all. The effect of pure ethanol is concentration-dependent.…”
Section: Alcohol Smoking and Stomachmentioning
confidence: 99%
“…magnesium, calcium, amines, phenols, amaroids, vitamins, and L -amino acids) were found to be responsible for the stimulatory effect [44]. Teyssen et al [45] have shown that the substances responsible for the maximal gastric acid secretion in fermented beverages are succinic acid and maleic acid, produced during the process of alcoholic fermentation, and that gastrin does not mediate their effect. Alcoholic beverages produced by fermentation followed by distillation, such as most aperitifs and hard liquors, do not stimulate acid secretion [46].…”
Section: Non-alcoholic Compounds Of Alcoholic Beveragesmentioning
confidence: 99%
“…Therefore, non-alcoholic ingredients in beer and wine are most likely responsible for the stimulatory gastric action of these alcoholic beverages. The search for the stimulatory substances in alcoholic beverages revealed that the powerful stimulants of gastric acid output are the dicarboxylic acids maleic and succinic acid which are produced during the process of alcoholic fermentation [3] . The surprising finding of this investigation was that these dicarboxylic acids do not stimulate gastrin release.…”
Section: Effects Of Ethanol and Alcoholic Beverages On Gastric Acid Smentioning
confidence: 99%
“…For example, up to now in beer more than 2000 and in wine more than 1,000 organic and anorganic constituents were defined. As outlined in detail below at least on gastric acid secretion it has been convincingly demonstrated that alcohol and alcoholic beverages have markedly different effects [1][2][3] .…”
Section: Introductionmentioning
confidence: 99%